The Position Of Women In The Family Law According To Liberal Feminis - Nur Solikin; Eka Wulandari Larantika Mualim (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2022)
Historical facts reveal that thousands of years before Islam came, especially in the era of Jahiliyah, women were seen as not having complete humanity and therefore women did not have the right to speak out, did not have the right to work, and did not have the right to own property, this caused the feeling of shame to have daughters who resulting in the burial of innocent baby girls being buried alive is also an injustice due to wrong traditions. The results of this research are (1) The misunderstanding of society regarding the position of women in the family according to Siti Musdah Mulia is the result of wrongly interpreting this verse of the Koran due to several reasons. One of them is that in general, Muslims understand religion more dogmatically, the Islamic community obtains religious knowledge through lectures from the scholars', and (2) Musdah Mulia's basic thoughts are related to formulating the position of women in the family, including a) There are no differences in men -men and women. One of God's blessings is that all human beings, whether male or female, are equal, regardless of ethnicity, wealth, or social position. In God's view, man is valued only based on his obedience; b) the essence of Islamic teachings is to humanize humans and respect their sovereignty. and therefore must be recognized as natural; c) The essence of religious teachings is to humanize humans, respect humans and honor them.